Efeito do selênio (Se) sobre o aparato fotossintético de Billbergia zebrina (Herbet) Lindley (Bromeliaceae) in vitro e sua ação atenuante frente ao estresse por zinco (Zn) - Souza, André Felipe Costa (2018)
Despite the beneficial effects, selenium (Se) is not an essential element for plants and its action mechanisms are still unclear. Zinc (Zn), in turn, is an essential micronutrient involved in various cellular functions. Excess Zn can be toxic to plants and Se, through different detoxification mechanisms, has been cited as an attenuating to the deleterious abiotic factors effects such as heavy metals. In this context, it was proposed to characterize the Se action on the Bilbergia zebrina (Herbert) Lindley photosynthetic apparatus and its potential attenuating action against the excess and scarcity of Zn in vitro. In the first experiment, B. zebrina lateral shoots were grown in MS medium with different concentrations of selenium (0, 2, 4 and 16 μM). After 75 days the photosynthetic pigments concentration, growth traits and chlorophyll a fluorescence were evaluated. This study demonstrated that in low concentrations, selenium increases the photosynthetic apparatus potential energy conservation capacity, maintains the FSII energy transport reactions stability and improves the electron transport dynamics between the intersystem and the FSI. Still, we observed that B. zebrina does not tolerate concentrations equal to or greater than 16μM of selenium, presenting reductions in growth, photosynthetic pigments content and photosynthetic apparatus impairment. In the second experiment, B. zebrina lateral shoots were cultured in MS medium with different Zn concentrations isolated (0, 30 and 300 μM) and combined with 4 μM Se (0 + Se, 30 + Se and 300 + Se μM), defined from previous studies After 75 days, the nutritional status of the samples, the concentration of photosynthetic pigments and the chlorophyll a fluorescence were evaluated. This second study demonstrated that Se gives the B. zebrina photosynthetic apparatus the ability to improve the energy utilization, stabilizing the dynamics of absorption, capture and transport. Thus, independen of the Zn scarcity or excess, Se protects FSII functions. Furthermore, according to the JIP test, the Zn absorption proportional to the concentrations used, did not cause significant interferences in the photosynthetic apparatus functionality or structure. Thus, it can be considered that the species B. zebrina exhibits eventual capacity for Zn accumulation, thus presenting potential characteristics for biomonitoring.